2018
DOI: 10.1371/journal.pone.0198189
|View full text |Cite
|
Sign up to set email alerts
|

A time series of urban extent in China using DSMP/OLS nighttime light data

Abstract: Urban extent data play an important role in urban management and urban studies, such as monitoring the process of urbanization and changes in the spatial configuration of urban areas. Traditional methods of extracting urban-extent information are primarily based on manual investigations and classifications using remote sensing images, and these methods have such problems as large costs in labor and time and low precision. This study proposes an improved, simplified and flexible method for extracting urban exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Night-time lighting images can describe the spatial distribution of urban economy and population, the main methods include statistical analysis method, clustering anal-ysis method, spatial constraint method, extraction results have the advantage of high integrity [18][19][20]. However, there is a light spillover effect in the night-time light images, which makes the extraction results have a high false detection rate.…”
Section: Night-time Lighting Datamentioning
confidence: 99%
“…Night-time lighting images can describe the spatial distribution of urban economy and population, the main methods include statistical analysis method, clustering anal-ysis method, spatial constraint method, extraction results have the advantage of high integrity [18][19][20]. However, there is a light spillover effect in the night-time light images, which makes the extraction results have a high false detection rate.…”
Section: Night-time Lighting Datamentioning
confidence: 99%
“…Several studies used data from arbitrarily delineated areas obtained by the government, land surveying, or land use classification from remote sensing to represent urban land areas for calculating land urbanization [43]. However, this approach may induce bias or limitation because urbanized land is neither defined by the government nor confined to its superficial or spectral attributes.…”
Section: Calculation Of Land Urbanization Ratementioning
confidence: 99%
“…The application of corrected DMSP/OLS nighttime data with stable lights has been welldocumented . Publicly accessible corrected DMSP/OLS nighttime data are also available [38,39]. We found that the corrected DMSP/OLS data adopted in the existing literature is too coarse to capture the features of developed land and associated nighttime brightness indices.…”
Section: Uncertainty In Enhanced Dmsp/ols Due To Data Sources and Metmentioning
confidence: 99%